SALINITY TOLERANCE OF CERTAIN FRESHWATER FISHES - Kasim, H Mohamad (Indian Journal of Fisheries, 2011)
To Rhinomiigil corsula (Hamilton) salinities below 12.25 %. (S) are not lethal at any temperature within the tolerance limit, in acute exposure from freshwater. The optimum temperatures from 26 to 30Â°C favour salinity tolerance. Low temperature is more detrimental than high, though this species has higher resistance times at low temperature. Sarotherodon mossambica Peters resists salinity better than common carp and freshwater mullet, Among carps, the common carp is highly tolerant to salinity, mrigal is the least tolerant and fringelipped carp is intermediate. Salinity acclimation in the fringelipped carp has enhanced only the resistance to salinity and there is no change in the tolerance level.